Scientific opinion on flavouring group evaluation 414 (FGE.414): 2‐hydroxy‐4‐methoxybenzaldehyde - EFSA Panel on Food Additives and Flavourings (FAF) (Wiley, 2021)
Abstract The EFSA Panel on Food Additives and Flavourings (FAF) was requested to evaluate the safety of the substance 2‐hydroxy‐4‐methoxybenzaldehyde [FL‐no: 05.229] as a new flavouring substance, in accordance with Regulation (EC) No 1331/2008. 2‐Hydroxy‐4‐methoxybenzaldehyde belongs to chemical group 23 (Commission Regulation (EC) No 1565/2000) and is structurally related to the hydroxy‐ and alkoxy‐ring substituted benzyl derivatives evaluated in FGE.52 and in FGE.20Rev4. The Panel considered the structural/metabolic similarity sufficient to evaluate the candidate substance following a group‐based approach according to the EFSA Guidance on the data required for the risk assessment of flavourings to be used in or on foods. The information provided on the manufacturing process, the composition and the stability of [FL‐no: 05.229] was considered sufficient. From studies carried out with this substance, the Panel concluded that there is no concern with respect to genotoxicity. Based on QSAR evaluation of possible metabolism, and based on information from structurally related substances, various metabolic routes can be anticipated, which only result in the formation of innocuous metabolites. The exposure estimates for [FL‐no: 05.229] (24 and 60 μg/person per day for children and adults, respectively) were below the Threshold of Toxicological Concern (TTC) for its structural class (I). Accordingly, toxicity studies are not required and the Panel concluded at step A3 of the Procedure that 2‐hydroxy‐4‐methoxybenzaldehyde is not of safety concern when used as a flavouring substance at the intended uses and use levels. Cumulative exposure estimates for 2‐hydroxy‐4‐methoxybenzaldehyde and three structurally related substances (2.4 and 6.2 mg/kg body weight (bw) per day for adults and children, respectively) are above the TTC for structural class I, but below the ADI (acceptable daily intake) of 0‐10 mg/kg bw per day for vanillin, which is one of these structurally related substances. Therefore, the cumulative exposure to these four substances [FL‐no: 05.015, 05.018, 05.229 and 09.749] also does not raise a safety concern.